GEOLOGY MODEL & RESERVOIR FACIES OF TELISA SANDSTONE IN KAJI â SEMOGA FIELDS, SOUTH SUMATERA BASIN. - LAURELL TARIGAN, RUDHY
The Telisa sandstone unit in Kaji – Semoga field is a sediment of Lowstand system track, and this sediment is known as the best reservoir for oil and gas. This unit consists of 4 (four) lithofacies : lithofacies-A, lithofacies-B, lithofacies-C, and lithofacies-D. The Telisa sandstone unit is a barrier sand sediment in Kaji field, and in Semoga field a Tidal sand flat sediment, so this unit ( Telisa sand ) has potential as a stratigraphic trap or combination of structural trap and stratigraphic trap. Distribution of the Tidal sandstone sediment is very varied and influenced by the reservoir heterogeneities and reservoir qualities, so the permeability barrier factor is very important because of the stimulation process. Study results using a geological model and reservoir facies from the Telisa sandstone indicate that the best producing hydrocarbons are lithofacies-C and lithofacies-D, especially in Kaji field, both of these are deposited as a Bar sand sediment and Tidal flat sand sediment, while in Semoga field the lithofacies-C and lithofacies-D are tidal sand flat with very high clay content. On the other hand, lithofacies-A and lithofacies-B seldom have produced hydrocarbon in either Kaji or Semoga fields. The results from hydraulic fracturing in the central part of Kaji field are better than those from the surrounding area, because the reservoir quality, resistivity and clay content are better than in Semoga field. The fact that production at Kaji is much higher than Semoga field proves this.